NILs in the genetic background of IR 64 and Sahel108 having introgressed the actpk1 gene that increases ammonia uptake. - CGIAR Research Program on Rice (2021)
NILs in the genetic background of IR 64 and Sahel108 having introgressed the actpk1 gene that increases ammonia uptake were evaluated under irrigated conditions. Grain yield increased by 11 to 17% in Sahel108-NILs.